Impact of Estrogen Therapy on BRCA1-Associated Breast Cancer Progression in Transgender Women - Muhammad Hamza Mubarak; Muhammad Kharisma (International Journal of Health and Medicine, 2024)
The combination of hormone treatment and genetic liabilities in transgender women leads to a complicated situation for breast cancer growth particularly linked to BRCA1 mutations. Gender-affirming treatment relies heavily on estrogen and causes intense cell growth and differentiation in breast tissue driven by estrogen receptor mechanisms. Mutations in BRCA1 lead to weak DNA repair processes which enhance an individual's vulnerability to cancerous changes. Rodestrogens enhance the functioning of proliferative pathways like PI3K/AKT and MAPK pathways in cells with dysfunctional BRCA1. This collaborative action elevates the threats posed by benign growths such as fibroadenomas leading to invasive breast cancer. By affecting the expression of vital regulatory proteins linked to cell proliferation estrogen further compromises the genomic integrity in cells harboring BRCA1 mutations. The hormone environment influenced by exogenous estrogen therapy can shape the tumor microenvironment for better cancer progression and metastasis. Comprehending the relationship between estrogen signaling and pathways related to BRCA1 is important for identifying the enhanced risk of cancer in transgender women using hormone therapy. This detailed study aligns recent discoveries regarding genetic vulnerability and hormonal impacts with cell mechanisms to reveal a detailed insight into breast cancer progression in these individuals. The study emphasizes the necessity for custom-designed cancer screening methods and targeted treatments to help mitigate risks and support transgender care. Understanding these pathways greatly enriches our knowledge of hormone-induced carcinogenesis among those who carry certain genetic markers while also guiding the creation of personalized care for transgender women at enhanced risk of breast cancer.